Design and Construction of A Web-Based Application for Managing Documents for Appointing CPNS to Civil Servants at The Regional Personnel Agency (BKD) of DKI Jakarta Province - Wibowo, Ari Purnomo Aji; Hartawan, Rumadi; Sianipar, Anton Zulkarnain; Narji, Mohammad (Jurnal Teknologi Informatika dan Komputer, 2025)
The development of information technology has encouraged changes in the management of personnel services that were carried out manually to a document management information system, to simplify the process of appointing CPNS to PNS at the Jakarta Civil Service Agency (BKD). The application of the document management system for appointing CPNS to PNS is a document management system created to organize and manage important letters or documents so that these documents are easy to search and find again. The Document Management System is useful in making business processes more effective and efficient. The main benefit is that users can find the information they need quickly, thus helping the process to be better and more efficient. This Document Management System can handle the recording of incoming CPNS documents, to each section at the Regional Civil Service Agency (BKD) of DKI Jakarta Province. With this Document Management System, it is expected to correct errors in recording transactions, prevent document loss and make work faster so that there are no obstacles and constraints in handling caused by human resource errors. This computerized system uses a website-based system, so its use must use a user login. Because the documents discussed here are confidential CPNS documents for the DKI Jakarta Provincial Civil Service Agency (BKD), they are expected to assist admins in serving users with their required data requests.